2017
DOI: 10.18823/asiatefl.2017.14.4.7.687
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Effect of Training on Raters’ Bias toward Test Takers in Oral Proficiency Assessment : A FACETS Analysis

Abstract: Typically, variability among raters in scoring and their bias is mediated through rater training. However, questions still remain about whether training can affect raters' severity or leniency. Furthermore, few studies have looked at the differences between trained and untrained raters in oral assessment. Oral test scores of 200 test takers rated by 20 raters and were analyzed before and after a training program using the multifaceted Rasch measurement (MFRM). The results demonstrated the constructive impact o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 30 publications
0
0
0
Order By: Relevance
“…This level may not correspond to the candidate's inherent ability due to the fact that the IELTS Speaking test is administered by a single rater Karim & Haq, (2014). Test raters might be classified as either "the difficult interviewers" or "the easy interviews," according to Bijani, H., & Khabiri (2017). In particular, difficult interviewers place an emphasis on the complex abilities of speculating and defending ideas.…”
Section: Marker Variabilitymentioning
confidence: 99%
“…This level may not correspond to the candidate's inherent ability due to the fact that the IELTS Speaking test is administered by a single rater Karim & Haq, (2014). Test raters might be classified as either "the difficult interviewers" or "the easy interviews," according to Bijani, H., & Khabiri (2017). In particular, difficult interviewers place an emphasis on the complex abilities of speculating and defending ideas.…”
Section: Marker Variabilitymentioning
confidence: 99%
“…In like manner, a study by Bonk and Ockey (2003) found that the more experience the raters obtain, the higher their standards are raised. In addition, the experienced raters tend to have more bias than inexperienced raters even after the training (Bijani & Khabiri, 2017). However, the harsh rater in this study conformed to the group agreement and is not considered a threat to the assessment.…”
Section: Discussionmentioning
confidence: 62%
“…Similarly, utilizing the result from the MFRM to inform each rater's performance in assessing can lessen the raters' judgment effect (Bonk & Ockey, 2003). Based on previous studies (Bijani & Khabiri, 2017;Bonk & Ockey, 2003;Eckes, 2009), good training sessions should offer the raters the detail of their rating performance, which can be obtained from MFRM.…”
Section: Discussionmentioning
confidence: 99%